2020
DOI: 10.1159/000506524
|View full text |Cite
|
Sign up to set email alerts
|

Association of Trichorhinophalangeal Syndrome and Loose Anagen Syndrome: A Case Report

Abstract: Trichorhinophalangeal syndrome (TRPS) is an autosomal dominant disease characterized by trichologic, craniofacial, and musculoskeletal abnormalities. Predominant clinical features include a pear-shaped nose with bulbous tip, long philtrum, protruding ears, and sparse hair on both the scalp and the lateral third of the eyebrows. Cone-shaped epiphyses are a common radiographic finding. Loose anagen syndrome (LAS) is a sporadic or autosomal dominant condition due to abnormalities in the hair’s anchoring mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Type III, also known as Sugio-Kajii Syndrome, is similar to type I with more prominent symptoms, more marked growth delay, and more severe shortness of fingers and toes. Therefore, it is considered a severe form of TRPS (2,8). In this study, we report a 15-yearold girl with TRPS1 and the second reported case with a rare non-ossifying fibroma (NOF) in the distal part of her left femur.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Type III, also known as Sugio-Kajii Syndrome, is similar to type I with more prominent symptoms, more marked growth delay, and more severe shortness of fingers and toes. Therefore, it is considered a severe form of TRPS (2,8). In this study, we report a 15-yearold girl with TRPS1 and the second reported case with a rare non-ossifying fibroma (NOF) in the distal part of her left femur.…”
Section: Introductionmentioning
confidence: 88%
“…All these three types are inherited as AD diseases with high penetrance and various clinical signs and symptoms depending on the pattern of mutation in the TRPS1 gene (1,6). Craniofacial features entail a thin upper lip with a horizontal smile, the bulbous or round tip of the nose, flat philtrum, maxillary prognathism and micrognathia, as well as large and protruding ears (7,8). Ectodermal abnormalities in these patients present as sparse and slow-growing hairs, especially in the temporal or occipital areas resembling androgenic alopecia, and the recession of the frontotemporal or occasionally occipital hairline (7,9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations